Effects of Chinese herbal medicine and cold exposure on plasma glucose, leucine and energy metabolism in sheep. Issue 2 (7th October 2017) - Liang, X.; Jin, J.; Bi, X.; Kamruzzaman, M.; Kudo, T.; Sano, H.
Summary: An experiment was carried out to assess the feeding effect of Chinese herbal medicine on N balance, ruminal fermentation characteristics, kinetics of plasma glucose, leucine and energy metabolism in sheep kept at thermoneutral environment (23°C) or exposed to cold (2–4°C). Four sheep were subjected to either mixed hay (MH‐diet) or hay supplemented with 2% of a traditional nourishing Chinese herbal medicine mixture (Astragalus root, Angelica root and Atractylodes rhizome; CHM‐diet) over two 23‐day periods using a crossover design. Cold exposure was conducted for 5 days. The isotope dilution of [U‐ 13 C]glucose with open circuit calorimetry was used to determine the turnover and oxidation rates of plasma glucose and metabolic heat production. The rate of plasma leucine turnover was measured with an isotope dilution method using [1‐ 13 C]leucine. N intake was higher, N excretion through faeces was lower and N digestibility was higher for the CHM‐diet than the MH‐diet. Rumen pH was lower, concentration of rumen NH3 was higher, concentrations of rumen total VFA and acetate tended to be higher and propionate was higher for the CHM‐diet compared with the MH‐diet. Turnover rate of plasma glucose was higher for the CHM‐diet than the MH‐diet and increased during cold exposure. Oxidation rate of plasma glucose did not differ between diets and also between environments. Turnover rate of plasma leucine was higher for the CHM‐diet compared with the MH‐diet but remained similar between environments. Heat production was greater for the CHM‐diet than the MH‐diet and increased during cold exposure. No significant diet × environment interaction was detected. The present results demonstrated that plasma glucose and energy metabolism were enhanced by both Chinese herbal medicine and cold exposure; plasma leucine metabolism was enhanced by Chinese herbal medicine but with lack of change in response to cold exposure in sheep under the conditions of the current experiment.